A Legally Binding Regime for the Arctic - Stefán Þór Hauksson (2009)
Currently there is no single comprehensive legal regime governing the Arctic region that compares to the Antarctic Treaty System. The Ilulissat declaration in 2008 stated that the Law of the Sea Convention is providing solid foundation responsible management. The main focus of this paper will be to answer whether or not it is necessary to implement a binding legal regime to the Arctic region. During the last fifty years a significant decrease in the quantity of ice has been measured due to increased global and regional temperature. The consequences of this development are among other things that seasonal freight routes are beginning to be accessible for longer periods each year. It also means easier access to natural resources such as oil, gas, marine species and various raw materials. Industrial activities all over the world are likely to bring outside pollutants to an ecosystem that is especially fragile because of the cold weather conditions that leads to slow decomposition of chemicals and slow regeneration of plants. The current legal regime seems unperfected when it is compared to the Antarctic Treaty System (ATS). It is made up from non-binding soft law legal bodies such as the Arctic Environmental Protection Strategy (AEPS) that later developed into the Arctic Council. The Law of the Sea Convention (UNCLOS) is legally binding on nations who have ratified and forms the only legal framework for cooperation forums and future development in laws in the Arctic. Creating a comprehensive legal regime for the Arctic similar to the one in the Antarctic would most defiantly take many years to form and would not be an easy project. Many scholars have suggested that it would be better to focus on strengthening the soft law regime in relation to the UNCLOS.